A Possible Common Physics Picture Reflected by the Gamma-Ray Emission of the Galactic Center - Lin Nie; Yi-Qing Guo; Si-Ming Liu (The Astrophysical Journal, 2025)
Long-term observations of the Galactic center by Fermi and HESS have revealed a novel phenomenon: the high-energy gamma-ray spectrum from the gamma-ray source HESS J1745-290 exhibits a double power-law structure. In this study, we propose a new explanation for this phenomenon. We suggest that the low-energy (GeV) power-law spectrum originates from interactions between trapped background “sea” cosmic ray particles and the dense gaseous environment near the Galactic center. In contrast, the bubble-like structure in the high-energy (TeV) spectrum is produced by protons accelerated during active phases of the Galactic center, through the same physical process. Based on this framework, we first calculate the gamma-ray emission generated by cosmic ray protons accelerated in the Galactic center. Then, using a spatially dependent cosmic ray propagation model, we compute the energy spectrum of background “sea” cosmic ray protons and their associated diffuse gamma-ray emission in the Galactic center region. The results closely reproduce the observations from Fermi-LAT and HESS, suggesting that their long-term data support this picture: high-energy cosmic rays in the local region originate from nearby cosmic ray sources, while low-energy cosmic rays are a unified contribution from distant cosmic ray sources. We anticipate that this double power-law structure may be widely present in the halo of a Galactic cosmic-ray source or a slow-diffusion region. We hope that future observations will detect more such sources, allowing us to further test and validate our model.